Composition and Dynamics of Bacterial Communities in a Full-Scale Mineral Water Treatment Plant - Wei, Lei; Wu, Qingping; Zhang, Jumei; Guo, Weipeng; Gu, Qihui; Wu, Huiqing; Wang, Juan; Lei, Tao; Chen, Moutong; Wu, Musheng; Li, Aimei (Frontiers in Microbiology, 2019)
The aim of this study was to gain insight into the bacterial composition and dynamics in a mineral water treatment system (MWTS). The bacterial community of a full-scale mineral water treatment plant in the Maofeng Mountain, South China, was studied using high-throughput sequencing combined with cultivation-based techniques in both the dry and wet season. Overall, adenosine tri-phosphate (ATP) concentration (6.47 × 10-11 – 3.32 × 10-8 M) and heterotrophic plate counts (HPC) (3 – 1.29 × 103 CFU/mL) of water samples in the wet season were lower than those (ATP concentration 5.10 × 10-11 – 6.96 × 10-8 M, HPC 2 – 1.97 × 103 CFU/mL) in the dry season throughout the whole MWTS. The microbial activity and biomass of water samples obviously changed along with treatment process. All 300 isolates obtained using cultivation-based techniques were distributed in 5 phyla, 7 classes, and 19 genera. Proteobacteria accounted for 55.7% (167) of the total isolates, among which predominant genus was Pseudomonas (19.3%). Illumina sequencing analysis of 16s rRNA genes revealed 15 bacterial phyla (relative abundance >0.1%) as being identified in all water samples. Among these, Proteobacteria constituted the dominant bacteria microbiota in all water samples. A large shift in the proportion of Bacteroidetes, Actinobacteria, and Firmicutes was obtained during the treatment process, with the proportion of Bacteroidetes, Actinobacteria decreasing sharply, whereas that of Firmicutes increased and predominated in the final water product. The core microbiome, which was still present in whole MWTS comprised several genera including Pseudomonas, Acinetobacter, Clostridium, and Mycobacterium, that contain species that are opportunistic pathogens, suggesting a potential threat for mineral water microbiology safety. This study is the first to investigate the bacterial community of a full-scale mineral water treatment plant in China. The results provided data regarding the bacteria composition and dynamics in an MWTS, which will contribute to the beneficial manipulation of the mineral water microbiome.